A Comparison Thyroid Function Test Between Patient Group and Control Group Among Women Had Thyroid Disorders - Bushra Hassan Abood, Ahmed Jasim Alhussaynei (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thyroid disorders are more common in women, and it is associated with infertility, menstrual irregularities, and pregnancy loss among women of childbearing age. Objectives: Comparison thyroid function test between patient group and control group among women had thyroid disorders. Materials and methods: A sample of a case-control study consisting of (100) clients from two hospitals in Salah al-Din Governorate/Iraq. The study was conducted during the period from(31th of October 2021 to 2th of August 2022) included obtaining a blood sample for thyroid function tests. Data were analyzed using SPSS software v.25.0 and Microsoft office 2010. Results: The results of the study showed hypothyroidism mean ± std (TSH (19.458 ± 8.250), freeT3(1.374±0.623), freeT4(8.746±1.875) for both TSH, f T3 and f T4 P-value 0.05< 0.0001) compared with control group, hyperthyroidism (TSH (0.095±0.059 ), freeT3(10.828±3.089), freeT4(28.303±3.137) for both TSH, f T3 and f T4 P-value 0.05< 0.0001) compared with control group, subclinical hyperthyroidism (TSH(0.221±0.045, p- value 0.05 < 0.0001), freeT3(3.945±1.102), freeT4(16.035±1.579) p-value 0.05> 0.7, 0.9 respectively compared with control group, subclinical hypothyroidism (TSH(7.889±1.900, p- value 0.05 < 0.0001), freeT3(3.893±1.060), freeT4(15.281±1.927) p-value 0.05> 0.06, 0.3 respectively compared with control group. Conclusions: There was a very high statistical significance with hypothyroidism and hyperthyroidism for both TSH, free T3 and T4 compared to control group, and also there was a very high statistical significance with subclinical hypothyroidism and subclinical hyperthyroidism for TSH, while no statistically significant for f T3 and f T4 compared to control group. Recommendations: The study advises all women with thyroid disorders to treat them of all kinds because of their impact on all body functions. Keywords: Thyroid disorders, Reproductive age group.